1994
DOI: 10.1021/ie00033a010
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Factors in K and Al Promoting of the Fe/MgO Fischer-Tropsch Catalyst

Abstract: The activity of Kand Al-promoted Fe/MgO catalyst for Fischer-Tropsch synthesis was measured under atmospheric pressure, with the aim to determine the promoter's influence on the catalyst selectivity, particularly in terms of olefins and isomers of lower hydrocarbons. The results have been correlated to the data of a previous study on the same catalyst, made under elevated pressure and designed for the alcohol production. It has been concluded that the promoting effect of K should be attributed to a geometric i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In addition to SiO 2 , other oxides, including ZrO 2 , Al 2 O 3 [118], MgO [119], CeO 2 [120], or Nb 2 O 3 [121] were used as support. Wan et al studied the Fe-Al 2 O 3 interaction over the precipitated iron catalyst in a slurry reactor and concluded that alumina inhibited the weak H 2 adsorption on iron surface but favored strong H 2 adsorption [122].…”
Section: Oxide Support Effectmentioning
confidence: 99%
“…In addition to SiO 2 , other oxides, including ZrO 2 , Al 2 O 3 [118], MgO [119], CeO 2 [120], or Nb 2 O 3 [121] were used as support. Wan et al studied the Fe-Al 2 O 3 interaction over the precipitated iron catalyst in a slurry reactor and concluded that alumina inhibited the weak H 2 adsorption on iron surface but favored strong H 2 adsorption [122].…”
Section: Oxide Support Effectmentioning
confidence: 99%